Altered Spatiotemporal Dynamics of the Resting Brain in Mild Cognitive Impairment with Lewy Bodies. Issue 10 (3rd August 2021) - Lamoš, Martin; Morávková, Ivona; Ondráček, David; Bočková, Martina; Rektorová, Irena
ABSTRACT: Background: Electrophysiological markers of prodromal dementia with Lewy bodies were described in the spectral domain. The sub‐second temporal resolution may provide additional information. Objective: To evaluate electroencephalography (EEG) microstates in patients with mild cognitive impairment with Lewy bodies and to assess the association between their temporal dynamics and the spectral marker. Methods: Temporal parameters of microstates were compared between 21 patients with mild cognitive impairment with Lewy bodies and 21 healthy controls. The dominant alpha frequency was correlated with microstate parameters. Results: Microstates A‐D showed higher occurrence in the patient group. Microstate B additionally revealed shorter mean duration and increased time coverage; its occurrence correlated with the dominant alpha frequency in the patient group. Conclusions: Temporal dynamics of all EEG microstates were altered in medication‐naïve subjects with prodromal dementia with Lewy bodies. Longitudinal follow‐up may reveal how EEG microstates reflect progression of brain function deficits and effects of treatment manipulations. © 2021 International Parkinson and Movement Disorder Society